Investigation of pressure distribution in an Archimedes Screw Turbine with head below one meter using CFD - Maulana, Muhammad Ilham; Sary, Ratna; Syuhada, A.; Mayasari, Siska; Yusmanizar, Yusmanizar (Jurnal Polimesin, 2024)
In the shift from fossil fuel-based energy, the imperative of tapping into water resources as a renewable energy reservoir is underscored. This study delves into the potential of low-head water for small-scale power generation, specifically focusing on the Archimedes turbine designed for operation in such conditions. The primary objective is meticulously examining pressure characteristics at varying heads (0.7 m, 0.8 m, 0.9 m, and 1 m) using Computational Fluid Dynamics (CFD). These parameters play a crucial role in defining the turbine's performance landscape. Data analysis reveals a notable reduction in the Archimedes turbine's efficiency as the head diminishes. Interestingly, the double-screw Archimedes turbine demonstrates optimal performance at higher flow rates, particularly at a volumetric flow rate of 0.025 m3/s. Despite the peak performance at a 1-meter head, discernible pressure patterns suggest sufficient kinetic energy within lower head flows (down to 0.7 meters) to facilitate turbine rotation. This study contributes to a more rigorous understanding of the Archimedes turbine's performance under varied head conditions, emphasizing the potential for practical power generation at lower head levels.